Organisation of Suburban and Urban Railway Traffic in the Krapina-Zagorje County and the City of Zagreb - Brkić, Alojz; Švaljek, Ivan; Jenić, Vinko (Promet - Traffic&Transportation, 2012)
Numerous inhabitants of the Krapina-Zag01je county fulfiltheir needs (work, education, trade) in the City of Zagreb. Themain passenger streams are related to railway transportationwhich, due to insufficient investments in the infrastructure andtransportation means, shows decrease in the service quality. Amodel is proposed for organising suburban and urban railwaytransp011ation in the Krapina-Zag01je county and the City ofZagreb, which would offer better quality in transportation services,increase economic efficiency of railway transp01tation,and thus eliminate the 1isk of having to close down cerlain railroadsin the county.